2010
DOI: 10.1248/cpb.58.61
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Principles from the Stem and Root Barks of Citrus medica

Abstract: Bioassay-guided investigation of the anti-inflammatory principles from the stem and root barks of Citrus medica L. var. sarcodactylis SWINGLE has led to the isolation of a new coumarin, namely citrumedin-B (1) and thirty known compounds. The anti-inflammatory components were xanthyletin (2), nordentatin (3), atalantoflavon (4) and lonchocarpol A (5) which displayed potent nitric oxide (NO)-reducing activity in microglial cells. The structure of this new compound was completely elucidated using a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 45 publications
1
30
0
2
Order By: Relevance
“…Results of qualitative phytochemical screening in (table 1) clearly demonstrated the presence of number important active constituents. Presence of carbohydrates, flavonoids, phenols, steroids and absence of saponins, anthraquinones, coumarin in Citrus medica in agreement with previously recorded data (Kabra et al, 2012;Chan et al, 2010), while presence of tannins, cardioactive glycosides in peel and juice and absence of alkaloids in peel of Iraqi species in contrast to the same study (Kabra et al, 2012) . The quantitative determination of plant bioactive constituents in this study the results showed in (table 2) revealed that phenolic content (21.18 & 9.38 mg/g dry extract) in Citrus medica was higher than flavonoid content (4.59& 1.44 mg/g dry extract) in peel and juice respectively are in accordance with those carried out in Riyadh, Saudi Arabia in which Citrus medica fruits showed high total phenol content (192.4 mg GA /100 g) than flavonoid values (74.1 mg quercetin /100 g) (Al-Yahya et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Results of qualitative phytochemical screening in (table 1) clearly demonstrated the presence of number important active constituents. Presence of carbohydrates, flavonoids, phenols, steroids and absence of saponins, anthraquinones, coumarin in Citrus medica in agreement with previously recorded data (Kabra et al, 2012;Chan et al, 2010), while presence of tannins, cardioactive glycosides in peel and juice and absence of alkaloids in peel of Iraqi species in contrast to the same study (Kabra et al, 2012) . The quantitative determination of plant bioactive constituents in this study the results showed in (table 2) revealed that phenolic content (21.18 & 9.38 mg/g dry extract) in Citrus medica was higher than flavonoid content (4.59& 1.44 mg/g dry extract) in peel and juice respectively are in accordance with those carried out in Riyadh, Saudi Arabia in which Citrus medica fruits showed high total phenol content (192.4 mg GA /100 g) than flavonoid values (74.1 mg quercetin /100 g) (Al-Yahya et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…When 1 was discovered [114], its bitter taste and some preliminary assays disguised it as an alkaloid probably suggesting to Berlays [115] the stem-in(e) which was commonly used for quinine-like compounds. Limonin has also recently been found in Citrus genus plant bark [25,116,117], and root [118], tissues. In addition to the above reported plants, 1 has been isolated from numerous non-Citrus species such as the endemic Brazilian species Raulinoa echinata [119], Glycosmis parva (a wild small shrub distributed in Thailand) [120], Poncirus trifoliata (a tree that is widely distributed in China) [121], and Dictamnus angustifolius [27,122,123].…”
Section: 2mentioning
confidence: 91%
“…In the last decade, delayed bitterness has continued to attract interest from several research groups and a number of papers have been dedicated to studies on mechanisms underlying delayed bitterness [10][11][12][13][14], possible ways of reducing [15][16][17][18] or modulating [19][20][21][22][23] the formation of bitter limonoids [1] in citrus fruits and juice products. On the other hand, evaluation of biological activities of CLs have disclosed great potential for these phytochemicals that furnished the rational basis of traditional medicinal uses of CL-containing folk remedies [24][25][26][27][28][29] as well as modern nutraceutical products [29,30]. Obviously, taste is a biological answer to xenobiotics just like any other pharmacological effect and during studies on delayed bitterness, a new limonoid possibly endowed with peculiar biological activities was discovered (see Section 3).…”
Section: Complexity and Evolution Of Citrus Limonoid Researchmentioning
confidence: 99%
See 2 more Smart Citations